Blockchain Technology Application: Authentication System in Digital Education - Amitkumar; Sanni, M. Ifran; Apriliasari, Dwi (Aptisi Transactions On Technopreneurship (ATT), 2021)
The application of technology in various aspects of life has made it easy for many people. However, there are also shortcomings in the use of technology, one of which is security issues, both transactions and data. Given these issues in this paper, we propose blockchain technology for an authentication system that will protect data rights and interests and be safe from interference to store information in the form of confidential text, especially in the application of technology in education. From this writing, there are 2 benefits, the first is that all data stored in the education system is guaranteed and there will be increased trust from both parents, teachers and other parties due to the decentralized nature of blockchain.